The State of Cellular Adoptive Immunotherapy for Neuroblastoma and Other Pediatric Solid Tumors - Le, Thanh-Phuong; Thai, To-Ha (Frontiers in Immunology, 2017)
Research on adult cancer immunotherapy is proceeding at a rapid pace resulting in an impressive success rate exemplified by a few high profile cases. However, this momentum is not readily extended to pediatric immunotherapy, and it is not for lack of trying. Though reasons for the slower advance are not apparent, some issues can be raised. Pediatric cancer patients represent a distinct demographic group whose immune system is inherently different from that of mature adults. Treating pediatric patients with immunotherapy designed for adults may not yield objective clinical responses. Here we will present an update on adoptive T-cell and NK-cell therapies for neuroblastoma and other childhood solid tumors. Additionally, we will delineate key differences between human fetal/neonatal and adult immune systems. We hope this will generate interests leading to the discussion of potential future directions for improving adoptive cancer immunotherapy for children.